Saphenous Artery Perforator/Propeller Flap in the Reconstruction of Perigenual Soft Tissue Defects - Balakrishnan, T. M.; Narayanan, Aishwarya Vadakencherry Lakshmi; Jaganmohan, J. (Indian Journal of Plastic Surgery, 2019)
Introduction In this article, we investigate the saphenous artery perforator propeller flap for the reconstruction of perigenual defects. We describe the anatomy of the saphenous artery and the method of raising a perforator propeller flap based on our study and early clinical experience.Aim To assess the effectiveness of the saphenous artery perforator propeller flap in the reconstruction of perigenual defects.Materials and Methods A preliminary cadaver dissection and injection study was conducted to discern the anatomical details of the perforator system of the saphenous vessel in 35 cadaveric specimens in 18 fresh cadavers. From March 2016 to March 2018, 16 clinical cases (5 females and 11 males, in the average age group of 33.5 years) with perigenual defects were reconstructed with saphenous artery perforator propeller flap. They were followed up for an average period of 12.5 months.Results Cadaver study established anterior sartorial perforators as the dominant system of the saphenous vessel and brought to the forefront the type 2 blood supply of the saphenous nerve. All patients had well-settled flaps at the end of the follow-up period, with good return of knee function.Conclusion Saphenous artery perforator propeller flap is a viable option for the reconstruction of defects around the knee joint.Level of Evidence Type V, therapeutic study.
Keywords: perigenual soft tissue defects; saphenous artery perforator propeller flap; saphenous vessel; soft tissue defects of the knee